Construction of an inducible green fluorescent protein (GFP) gene in a binary vector - Noor Adzlina, Binti Abidin (Universiti Malaysia Sarawak, UNIMAS, 2013)
Green fluorescent protein (GFP) gene is synthesized by jellyfish Aequorea victoria and it is widely used as reporter gene in molecular biology studies. The discovery of this reporter gene contributes to the development in the gene expression, cell development and signal transduction studies. It also leads to the discovery of novel characteristics in a particular organism. The construction of inducible synthetic GFP into a binary vector was carried out by using the restriction enzyme digestion of the DNA fragments and followed by the ligation of the DNA fragments by DNA ligase. Both mechanisms were carried out in vitro. The binary vector was used in this research because it facilitates the transfer of the gene into a target organism via Agrobacterium- mediated transformation. Meanwhile, for the verification steps, the Polymerase Chain Reaction (PCR) was used to identify the integration of synthetic GFP gene in the binary vector. There were many Escherichia coli XL1 Blue colonies grew on the Luria Agar (LA) media containing antibiotic ampicillin. However, the PCR cannot verify the presence of sGFP gene in the pAGS3/sGFP plasmids harbored by the E. coli XL1 Blue colonies. The result indicated that there was an absence of pAGS3/sGFP plasmid in the transformed E. coli XL1 Blue.